BUDGET TREND DETERMINING WITH THE HELP OF ANGULAR OPERATIONS - Galina I. Bobrik (Plekhanov Russian University of Economics, 2017)
The article investigates the problem of operational measurement of demand and supply during exchange trade with the help of angular operations. For this purpose a small amount of asset is bought, which is sold later or these steps are conducted in reverse order. To get mathematically strict proof a multi-agent model of exchange pricing was used. The authors showed that as a result of an angular operation the price changes in the direction of the trend. Acceptability of this approach was analyzed, as well as its efficiency and reliability. In particular, it was shown that in conditions of demand and supply equilibrium angular operations cause no loss minus transaction costs and costs connected with spread between purchase and sale.